Answer:
x = (-39)/11
Step-by-step explanation:
Solve for x:
x - 9 = (3 (5 x + 1))/4
Multiply both sides by 4:
4 (x - 9) = (4×3 (5 x + 1))/4
(4×3 (5 x + 1))/4 = 4/4×3 (5 x + 1) = 3 (5 x + 1):
4 (x - 9) = (3 (5 x + 1))
Expand out terms of the left hand side:
(4 x - 36) = 3 (5 x + 1)
Expand out terms of the right hand side:
4 x - 36 = (15 x + 3)
Subtract 15 x from both sides:
(4 x - 15 x) - 36 = (15 x - 15 x) + 3
4 x - 15 x = -11 x:
-11 x - 36 = (15 x - 15 x) + 3
15 x - 15 x = 0:
-11 x - 36 = 3
Add 36 to both sides:
(36 - 36) - 11 x = 36 + 3
36 - 36 = 0:
-11 x = 3 + 36
3 + 36 = 39:
-11 x = 39
Divide both sides of -11 x = 39 by -11:
(-11 x)/(-11) = 39/(-11)
(-11)/(-11) = 1:
x = 39/(-11)
Multiply numerator and denominator of 39/(-11) by -1:
Answer: x = (-39)/11